FIDES Athlete Development Programme: project background and study protocol of an embedded multiple case study - Bård Erlend Solstad; Monica Klungland Torstveit; Sofia Ryman Augustsson; Anna Melin; Aron Laxdal; Ådne Ausland; Daniel Bjärsholm; Jørgen Bagger Kjær; Mariah Larsson; Susanne Linner; Felicia Radovan (BMJ Open Sport & Exercise Medicine, 2024)
Most sports science research revolves around male subjects. As a result, most of the knowledge and practices within sports are male-centric. Failing to take the biological, psychological and social (biopsychosocial) particularities of females into account is believed to hinder optimal sports participation, development and performance, with potential negative effects on the health and well-being of females. To close the knowledge gap and alleviate these issues, we aim to develop and evaluate a 12-video educational intervention that addresses female-specific subject matter: the FIDES Athlete Development Programme. The study is designed as an embedded multiple case study where at least 1320 Swedish female athletes aged 13–16 will participate, in addition to their parents and their coaches. The girls will be recruited through their sports clubs, with half being exposed to the FIDES Athlete Development Programme and the other half serving as control cases. The primary outcomes are well-being and sporting experience. To further increase our understanding of the intervention and its implications, interviews and focus group interviews with a reference group of girls and focus group interviews with a randomly selected subsample of coaches and parents will also be performed. The project is approved by the Swedish ethics committee (number: 2023-05264-01) and will be carried out in compliance with the Declaration of Helsinki. Results from the project will be published open access in peer-reviewed journals, at national and international conferences, in mass media, and a PhD thesis. The anonymised data will be made openly available in a data repository.